Purification, Structural Analysis and Cardio-Protective Activity of Polysaccharides from Radix Astragali - Shilei Wang; Yuan Peng; Yixin Zhuang; Nan Wang; Jianchang Jin; Zhajun Zhan (Molecules, 2023)
Two polysaccharides, named APS2-I and APS3-I, were purified from the water extract of Radix Astragali. The average molecular weight of APS2-I was 1.96 × 106 Da and composed of Man, Rha, GlcA, GalA, Glc, Gal, Xyl, and Ara in a molar ratio of 2.3:4.8:1.7:14.0:5.8:11.7:2.8:12.6, while the average molecular weight of APS3-I was 3.91 × 106 Da and composed of Rha, GalA, Glc, Gal, and Ara in a molar ratio of 0.8:2.3:0.8:2.3:4.1. Biological evaluation showed APS2-I and APS3-I had significant antioxidant activity and myocardial protection activity. Furthermore, total polysaccharide treatment could significantly enhance hemodynamic parameters and improve cardiac function in rat ischemia and reperfusion isolated heart models. These results provided important information for the clinical application of APS in the field of cardiovascular disease and implied that Astragalus polysaccharides (APS) could be considered as a reference for the quality control of Radix Astragali.